Nepal cerebral palsy register (NCPR): towards developing a platform for national cerebral palsy (CP) register and population - based surveillance of children with CP in Gorkha, Nepal. - Khandaker,Gulam (2019)
SUMMARY: Cerebral palsy (CP) is a group of non-progressive disorder that affects the immature brain of children leading to impaired motor function and childhood disability. CP is the leading cause of childhood disability worldwide and the burden is comparatively higher in low and middle income countries than the high income countries. In this study we aimed to conduct a population based surveillance of children with CP aged below 18 years in selected six municipalities of Gorkha district, Nepal. We adopted the key informant method (KIM) to identify children with suspected CP from the community by trained local volunteers known as Key Informants (KIs). A total of 174 KIs were trained to identify children with CP from their community as part of this study. Each of the children with suspected CP then underwent detailed neurodevelopmental assessment by a multidisciplinary medical assessment team including paediatricians and physiotherapist. The medical assessment team confirmed the diagnosis of CP and collected detailed information using a standard data collection form. In this study, a total of 213 children with suspected CP listed by the KIs attended the medical assessment camps and of them 181 children had confirmed CP. All of them underwent detailed neuro developmental assessment where their socio-demographic characteristics, pre & perinatal history, motor function, associated impairments, feeding difficulties, nutritional status, educational and rehabilitation status were documented. The children who could be benefitted from physiotherapy received an on spot session by a trained physiotherapist and their primary caregivers were provided hands-on training to continue these sessions at home. The study indicates a high burden of CP in the study sites and also the need of adequate rehabilitation services for betterment of the children. Similar studies should be conducted to generate evidence regarding the epidemiology of CP among children in Nepal.